Peran kepemimpinan yang memberdayakan pada perilaku kewargaan organisasi: Studi pada perusahaan swasta - Purba, Debora Eflina; Herlina, Graciela Minalesta (Institute for Advanced Social, Science, and Sustainable Future, 2024)
The social exchange theory explains how employees will reciprocate the good treatment given by their superiors by displaying positive behavior through organizational citizenship behavior (OCB), such as helping coworkers who are absent at work. The purpose of this research is to investigate the role of each dimension of empowering leadership, namely the meaningfulness of work, employee participation in decision-making, trust in employee performance, and granting autonomy to employees, positively and significantly predicts OCB. To answer the research question, a correlational study design using a survey was conducted on private sector employees in Indonesia. The number of survey participants was 301, with 164 female participants (54%) and 137 male participants (46%). The data were analysed using multiple linear regression analysis techniques with SPSS v.23. The results of the study indicated that only the dimensions of meaningfulness of work and trust in employee performance could positively and significantly predict OCB. Theoretical and practical implications are further discussed.